1977
DOI: 10.1063/1.89757
|View full text |Cite
|
Sign up to set email alerts
|

Instability of a low-pressure Na–noble-gas discharge

Abstract: A new type of discharge instability is reported for a low-pressure Na–noble-gas discharge (∼5×10−3 Torr Na; 5.5 Torr Ne-Ar, 1% Ar). The voltage-current (V-I) characteristic is shown to be multivalued in the voltage. The resulting instability is a discontinuity in the positive column which propagates in the direction of electron particle flow with velocity between about 105 and 5×105 cm/s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A detailed study of the sudden increase in electrical field due to the sodium depletion has shown that the voltage/current characteristic of low-pressure sodium lamps is multivalued at the critical current [50] (see Fig. 34), and that there is a minimum in the afterglow decay time of the lamp at the transition [51].…”
Section: O Pressure Metermentioning
confidence: 98%
See 1 more Smart Citation
“…A detailed study of the sudden increase in electrical field due to the sodium depletion has shown that the voltage/current characteristic of low-pressure sodium lamps is multivalued at the critical current [50] (see Fig. 34), and that there is a minimum in the afterglow decay time of the lamp at the transition [51].…”
Section: O Pressure Metermentioning
confidence: 98%
“…33 Measured radial concentration distribution of Cs in Cs-Ar low-pressure discharge at 378 K for three values of discharge current [49] I (A) Fig. 34 Measured V/l curve for sodium/rare-gas discharge showing its multivalued character [50] -t(ms) Fig. 35 Measured electric field E, electron temperature T e and axial electron density N e in sodium-neon discharge [53] 900 mA, 50 Hz, tube diameter 19 mm, neon pressure 730 Pa, tube-wall temperature 530 K and electron density have also been carried out on a discharge operating on a 50Hz supply [52,53].…”
mentioning
confidence: 98%